Kemandirian Belajar Siswa Pada Mata Pelajaran Dasar-Dasar Perbankan Dalam Prespektif Aktivitas Belajar Dan Pengorganisasian Tugas Terstruktur Kelas X Akuntansi Smk Negeri 1 Boyolali Tahun Ajaran 2016/2017 - Wahyuni, Sri; , Drs. Sudarto, HS., M.M (2017)
ABSTRACT The objectives of this study are to examine 1) the influence of learning activity towards students' learning independence, 2) the influence of structured task organization towards students' learning activity, 3) the influence of learning activity and structured task organizations towards students' learning independence. This research was using associative quantitative method in which the conclusion of the study was acquired based on statistic result where the result was laid out in numbers. Population which was used was class X Accounting SMK Negeri 1 Boyolali in the academic year of 2016/2017, amount to 108 students in which 86 students were taken to be the sample. This study was using random sampling technique with simple random sampling method. For collecting data technique, the researcher used questionnaire and documentation method. Previously, the questionnaire method had been through trial run by using validity test and reliability test. Data analysis technique which was used bifilar regression, t test, F test, effective contribution and relative contribution. The result of the research using regression analysis was obtained regression formula: Y = 15,007 + 0,038X1 + 0,652X2. The result concluded 1) there was significant influence between learning activity towards students' learning independence based on t test was acquired thitung> ttabel, which was7,447 > 1,989 and significant 5%, 2) there was significant influence between structured task organization and students' learning independence based on t test was acquired thitung> ttabel, which was 4,124 > 1,989, and significant 5%, 3) there was significant influence between learning activity and structured task organization and students' learning independence based on f test was acquired fhitung> ftabel, which was 14,478 > 3,11 with significant values 5%. The result of the research for R2 was acquired as many as 25,9% contains of 0,4389% for learning activity and 25,4508% for structured task organization, and the rest 74,1% was influenced by other variables which were not included in this research Keywords: Students' Learning Independence, Learning Activity, and Structured Task